2020
DOI: 10.1186/s40634-020-00278-y
|View full text |Cite
|
Sign up to set email alerts
|

Computer and robotic – assisted total knee arthroplasty: a review of outcomes

Abstract: Background Total knee arthroplasty (TKA) is a successful treatment for tricompartmental knee arthritis. Computer navigation and robotic-assisted-surgery (RAS) have emerged as tools that aim to help plan and execute surgery with greater precision and consistency. We reviewed the most current literature to describe the historical background and outcomes compared to conventional TKA. Methods A review and synthesis of the literature comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Navigation has therefore made it possible to reduce the degree of dispersion and achieve a neutral mechanical axis. Recent meta-analyses 32 have shown that navigation increases the safety and consistency of implant position, and that this has a beneficial effect on clinical and functional outcomes. This technique reduces asymmetric polyethylene wear, mobilization and sinking in of prosthetic components, particularly in young and active people, and prevents complications derived from the use of manual instrumentation [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Navigation has therefore made it possible to reduce the degree of dispersion and achieve a neutral mechanical axis. Recent meta-analyses 32 have shown that navigation increases the safety and consistency of implant position, and that this has a beneficial effect on clinical and functional outcomes. This technique reduces asymmetric polyethylene wear, mobilization and sinking in of prosthetic components, particularly in young and active people, and prevents complications derived from the use of manual instrumentation [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not robotic total knee arthroplasty leads to improved radiographic and clinical outcomes remains the subject of significant controversy [36]. Stated broadly, outcomes after robotic-assisted TKA can be grouped into either those related to accuracy and precision of component positioning and alignment or those related to clinical improvement, patient-reported outcomes (PROs), and functionality metrics.…”
Section: Discussionmentioning
confidence: 99%
“…PSI, CAN, and robotic-assisted techniques have also proved helpful in knee arthroplasty, where correct frontal, sagittal, and axial alignment of the prosthetic components is essential for the good function and longevity of the implant. New technologies allow more accurate and reproducible restoration of mechanical axis, component alignment, and soft tissue balance [ 113 ]. To shorten intraoperative radiation, the 3D-printed personalized guide in assisting the accurate drilling of K-wire has been developed in arthroscopic ankle arthrodesis [ 114 ].…”
Section: Computer-assisted Orthopaedic Surgerymentioning
confidence: 99%